Multiplexed and high-bandwidth DNA computing circuits with superresolution DNA origami displays - Zhongchao Jin; Yuqing Tang; Sisi Jia; Zheze Dai; Zhikun Zhao; Jiang Li; Kai Xia; Jun Liu; Ke Ke; Hui Lv; Qian Li; Fei Wang; et al. (Proceedings of the National Academy of Sciences, 2025)
DNA computing circuits leverage molecular interactions to construct a highly parallel and biologically compatible information processing paradigm. However, their development has been constrained by a critical gap between intrinsic computational parallelism and the limited readout bandwidth. Multibit outputs from complex circuits often require multiple separate tests, limiting the integration and debugging efficiency. Here, we overcome this bottleneck by decoupling computation from readout via a DNA origami display-based interface by integrating strand displacement and unstable binding reactions. We convert multibit molecular outputs from DNA circuits into spatially resolved geometric bits, enabling direct visualization via superresolution microscopy for high-throughput readout. We experimentally demonstrated the direct readout of an 8-bit decoder circuit and simultaneous display of 16 parallel-running logic gates. This high-bandwidth platform unlocks capabilities in circuit debugging and multiplexed execution, paving the way for large-scale DNA computing and high-throughput biosensing.